2022
DOI: 10.1007/s00705-022-05368-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigational antiviral drugs for the treatment of COVID-19 patients

Abstract: In the current pandemic of coronavirus disease 2019 (COVID-19), antiviral drugs are at the center of attention because of their critical role against severe acute respiratory disease syndrome coronavirus 2 (SARS-CoV-2). In addition to designing new antivirals against SARS-COV-2, a drug repurposing strategy is a practical approach for treating COVID-19. A brief insight about antivirals would help clinicians to choose the best medication for the treatment of COVID-19. In this review, we discuss both novel and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…[37] It has been demonstrated that ritonavir improves the efficacy of several ARVs. For instance, in HIVinfected individuals who had received therapy in the past as well as those who had never had it, the combination of lopinavir and ritonavir effectively decreased viral load and improved immunological markers [38,39]. Ritonavir is being explored in conjunction with antineoplastic medicines to treat cancer due to its mechanisms of action.…”
Section: Covid-19 Therapeutic Implications Of Ritonavirmentioning
confidence: 99%
“…[37] It has been demonstrated that ritonavir improves the efficacy of several ARVs. For instance, in HIVinfected individuals who had received therapy in the past as well as those who had never had it, the combination of lopinavir and ritonavir effectively decreased viral load and improved immunological markers [38,39]. Ritonavir is being explored in conjunction with antineoplastic medicines to treat cancer due to its mechanisms of action.…”
Section: Covid-19 Therapeutic Implications Of Ritonavirmentioning
confidence: 99%
“…The ongoing threat of viral infections, such as influenza virus [154], coronavirus disease 2019 (COVID-19) virus [155], and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus [156], underscores the importance of effective antiviral therapies in preventing disease spread, mitigating viral damage, and facilitating patient recovery. Antiviral drugs not only help control outbreaks and improve treatment outcomes but also minimize the risk of viral mutations and drug resistance.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…This intense selection pressure against the S protein leads to the appearance of variant mutations, thus decreasing the effectiveness of vaccines based on this protein [31] , [32] , [33] , [34] . Thus, other proteins with fewer variations may be better targets for facing this virus; Mpro as well as RNA-dependent RNA polymerase (RdRp) are two of these proteins mainly focused on, in the studies [35] , which are also exposed to possible mutations. Iketani and colleagues recently examined possible mechanisms of resistance to nirmatrelvir [36] .…”
Section: Nirmatrelvir and Sars-cov-2 Variantsmentioning
confidence: 99%